Point‐of‐Care Platform for Rapid Multiplexed Detection of SARS‐CoV‐2 Variants and Respiratory Pathogens. Issue 6 (7th January 2022) - Trick, Alexander Y.; Chen, Fan‐En; Chen, Liben; Lee, Pei‐Wei; Hasnain, Alexander C.; Mostafa, Heba H.; Carroll, Karen C.; Wang, Tza‐Huei
Abstract: The rise of highly transmissible SARS‐CoV‐2 variants brings new challenges and concerns with vaccine efficacy, diagnostic sensitivity, and public health responses to end the pandemic. Widespread detection of variants is critical to inform policy decisions to mitigate further spread, and postpandemic multiplexed screening of respiratory viruses will be necessary to properly manage patients presenting with similar respiratory symptoms. In this work, a portable, magnetofluidic cartridge platform for automated polymerase chain reaction testing in <30 min is developed. Cartridges are designed for multiplexed detection of SARS‐CoV‐2 with either identification of variant mutations or screening for Influenza A and B. Moreover, the platform can perform identification of B.1.1.7 and B.1.351 variants and the multiplexed SARS‐CoV‐2/Influenza assay using archived clinical nasopharyngeal swab eluates and saliva samples. This work illustrates a path toward affordable and immediate testing with potential to aid surveillance of viral variants and inform patient treatment. Abstract : A portable instrument integrates sample preparation with direct coupling to multiplexed polymerase chain reaction assays in a single magnetofluidic cartridge. This platform demonstrates identification of SARS‐CoV‐2 in patient swab and saliva samples with simultaneous screening for variants of concern or influenza A and B in less than 30 min.